The Effectiveness of the Local Knowledge-Based Module (LKBM) to Improve Students’ Scientific Literacy and Thinking Skills - Uslan, U.; Abdullah, N.; Imami, M. K. W.; Aiman, U. (Jurnal Pendidikan IPA Indonesia, 2024)
Scientific literacy is an essential 21st-century skill that students must master. Scientific literacy is the proficiency to engage with scientific ideas and knowledge that shapes the student’s ability to interpret and evaluate data within scientific inquiry and make decisions regarding natural change, human activities, and technology. In addition to scientific literacy, thinking skills are crucial in the current era. Thinking skills help students solve social, scientific, and practical problems. Therefore, the current research objective is to test the effectiveness of the local-based knowledge module as a learning media to enhance student scientific literacy and thinking skills in Kupang Regency. 78 elementary school students in Kupang, Indonesia, were involved. They were selected based on the random sampling method and divided into experimental and control groups. The data were collected before using the module, during the use of the module, and after using the module. The instrument used to collect the data was tested for validity and reliability with expert validation. The collected data was then analyzed with SPSS 16 package software. Descriptive analysis and MANOVA were performed. The results indicate that the students’ average scores in scientific literacy and thinking skills are enhanced after they use the module. It is emphasized by the significance of the MANOVA analysis, which indicates the difference in score between the group of students who use the local-based knowledge module and those who do not. Based on the results, the module effectively enhances students’ scientific literacy and thinking skills. Therefore, this module can be used by teachers at the learning level to improve their scientific literacy and thinking skills.